Pelestarian tari Zapin Pecah Duabelas melalui kegiatan ekstrakurikuler sekolah sebagai sarana pembelajaran dan internalisasi nilai budaya - Adjie Restu Winata; Andini Eka Hariyani; Ardhita Fahira Putri; Arkhensa Putri Nugianata; Putri Lusiani; Yoga Yolanda (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2026)
The Zapin Pecah 12 dance is a traditional Riau Malay performing art form with strong historical, religious, and sociocultural values. However, globalization and the dominance of popular culture have led to a decline in young people’s interest in traditional dance. This study aims to describe the preservation process of the Zapin Pecah 12 dance through extracurricular activities at SMA Negeri 11 Pekanbaru and to examine the role of this dance learning as a medium for transmitting Riau Malay cultural values. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results show that the Zapin Pecah 12 extracurricular activities play an important role in preserving Riau Malay Zapin art, particularly in the geographical context of Pekanbaru as a transitional area between coastal and inland cultures. The learning of this dance not only preserves the movement forms but also transmits religious values, discipline, togetherness, and Riau Malay cultural identity to the students.